Wounds Inhibit Tumor Growth In Vivo. Issue 1 (January 2021) - Hu, Michael S.; Maan, Zeshaan N.; Leavitt, Tripp; Hong, Wan Xing; Rennert, Robert C.; Marshall, Clement D.; Borrelli, Mimi R.; Zhu, Ted N.; Esquivel, Mikaela; Zimmermann, Andrew; McArdle, Adrian; Chung, Michael T.; et al.
Abstract : Objective: The aim of this study was to determine the interaction of full thickness excisional wounds and tumors in vivo. Summary of Background Data: Tumors have been described as wounds that do not heal due to similarities in stromal composition. On the basis of observations of slowed tumor growth after ulceration, we hypothesized that full thickness excisional wounds would inhibit tumor progression in vivo. Methods: To determine the interaction of tumors and wounds, we developed a tumor xenograft/allograft (human head and neck squamous cell carcinoma SAS/mouse breast carcinoma 4T1) wound mouse model. We examined tumor growth with varying temporospatial placement of tumors and wounds or ischemic flap. In addition, we developed a tumor/wound parabiosis model to understand the ability of tumors and wounds to recruit circulating progenitor cells. Results: Tumor growth inhibition by full thickness excisional wounds was dose-dependent, maintained by sequential wounding, and relative to distance. This effect was recapitulated by placement of an ischemic flap directly adjacent to a xenograft tumor. Using a parabiosis model, we demonstrated that a healing wound was able to recruit significantly more circulating progenitor cells than a growing tumor. Tumor inhibition by wound was unaffected by presence of an immune response in an immunocompetent model using a mammary carcinoma. Utilizing functional proteomics, we identified 100 proteins differentially expressed in tumors and wounds. Conclusion: Full thickness excisional wounds have the ability to inhibit tumor growth in vivo. Further research may provide an exact mechanism for this remarkable finding and new advances in wound healing and tumor biology. Abstract : Supplemental Digital Content is available in the text